2015
DOI: 10.2147/dmso.s54679
|View full text |Cite
|
Sign up to set email alerts
|

Anagliptin in the treatment of type 2 diabetes: safety, efficacy, and patient acceptability

Abstract: Anagliptin is a novel dipeptidyl peptidase-4 inhibitor that has been available in Japan since 2012. Because anagliptin is not generally used in countries other than Japan, there are only a small number of reports investigating the effects of anagliptin. In the present article, we review the safety and efficacy of anagliptin according to data obtained from preclinical trials and postmarketing studies. The usual dose of anagliptin is 200 mg daily, and increases in the dose up to 400 mg daily have been approved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 32 publications
1
26
2
Order By: Relevance
“…However, switching to anagliptin from other DPP-4 inhibitors such as sitagliptin, alogliptin, vildagliptin, linagliptin or teneligliptin exhibited no significant change in HbA1c levels after 12 and 24 weeks of treatment with anagliptin in 20 participants. In addition to the glucose-lowering effect, previous reports have shown that anagliptin has a lipid-lowering effect, decreasing the plasma total cholesterol, LDL-C and TG levels, which was indicated by pooled analysis of phase III clinical trials 30. However, in this study, administration of anagliptin showed no change in lipid data after both 12 and 24 weeks of treatment.…”
Section: Discussioncontrasting
confidence: 67%
“…However, switching to anagliptin from other DPP-4 inhibitors such as sitagliptin, alogliptin, vildagliptin, linagliptin or teneligliptin exhibited no significant change in HbA1c levels after 12 and 24 weeks of treatment with anagliptin in 20 participants. In addition to the glucose-lowering effect, previous reports have shown that anagliptin has a lipid-lowering effect, decreasing the plasma total cholesterol, LDL-C and TG levels, which was indicated by pooled analysis of phase III clinical trials 30. However, in this study, administration of anagliptin showed no change in lipid data after both 12 and 24 weeks of treatment.…”
Section: Discussioncontrasting
confidence: 67%
“…Our ex vivo data revealed that proportion of primitive EPCs was higher than definitive EPCs in PB and BM in DIO mice, indicating that obesity-induced inflammatory milieu decrease stem/progenitor cell differentiation in ischemic tissue due to unproductive inflammation, which supports other studies [23,30,31]. The DPP-4 inhibitors, such as Sitagliptin [32], Vildagliptin [33], Linagliptin [34], Teneligliptin [35], Anagliptin [36], Trelagliptin [37], and Omarigliptin [38] are already in use for clinical treatment of diabetes.…”
Section: Anti-inflammatory Effect Of Mk-0626 To the Ischemic Tissuesupporting
confidence: 88%
“…In patients with renal impairment, which is a very common complication of T2DM, sitagliptin is more suitable than sulfonylureas ( 100 ). Anagliptin, which is only approved since 2012 in the Japanese market, seems to have serum lipid-lowering and anti-atherogenic actions as well, which makes it unique among the gliptins approved so far ( 101 , 102 ). Anagliptin has an IC50 of 3.3 nM and its main excretion route is renal elimination ( 101 , 103 ).…”
Section: Enzymatic Function Of Dpp4mentioning
confidence: 99%